THE EFFECT OF MATURITY OF PROCUREMENT UNIT AGAINST CORRUPTION CASES IN INDONESIAN GOVERNMENT - Imelda Suardi (ADVANCED INTERNATIONAL JOURNAL OF BANKING, ACCOUNTING AND FINANCE (AIJBAF), 2024)
The maturity of the procurement unit has evolved substantially over the past decade. As part of procurement governance, the maturity of a procurement unit is a critical determinant in developing an efficient and corruption-free government procurement system. The paper examines the effect of the maturity of procurement units against corruption cases across Indonesian ministries, institutions, and provincial governments. The research uses the procurement governance index and procurement corruption cases data and analyses the variables using binary logistic regression of SPSS. The paper provides empirical results that higher level maturity of procurement units does not reduces the opportunity for corruption. It gives insights to the Indonesian government for the improvement of procurement units and the existence of procurement corruption during the years 2021-2023.